Effect of salt and fat reduction on proteolysis, rheology and cooking properties of Cheddar cheese. (May 2016) - McCarthy, Catherine M.; Wilkinson, Martin G.; Kelly, Philip M.; Guinee, Timothy P.
Abstract: Full-fat (FF, 33%), reduced-fat (RF, 22%) and half-fat (HF, 16%) Cheddar-style cheeses, each with full salt (FS, 1.9%), reduced salt (RS, 1.2%) or half salt (HS, 0.9%) variants, were made on three separate occasions. Reducing salt from 1.9 to 1.2 or 0.9% in the FF, RF and HF cheeses resulted in lower intact casein, firmness, fracture stress and work to extend the molten cheese, and higher heat-induced flow. The fracture strain of the RF and HF cheeses increased while that of the FF cheese decreased on reducing salt content. The results show the response to reducing salt depended on the variable studied, extent of salt reduction and fat level. Generally, reducing fat had opposite effects to those of salt reduction. There was a significant interaction between salt and fat content on the fracture characteristics, heat-induced flow, and extensibility of molten cheese at ripening times ≥90 d.